2011
DOI: 10.1902/jop.2010.100388
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Analysis of Relative Position Between Implant and Alveolar Bone: Finite Element Method

Abstract: Both loading type and implant position were crucial for stress distribution in bone. The supracrestal 1 implant position may not be ideal to avoid overloading the alveolar bone surrounding implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
18
0
4
Order By: Relevance
“…12 Moreover, the peak compressive stress has been found to provide more reliable information in the analysis of bone resorption compared with the peak tensile stress. 10 Therefore, bone resorption due to overloading should be expected when the compressive stress exceeds 100 to 130MPa in the cortical bone. 21 In the present study, the implant placed at the crestal level (BO model) exerted a peak compressive stress of 233.9 MPa under centric loading, which is above the physiological limit for cortical bone tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Moreover, the peak compressive stress has been found to provide more reliable information in the analysis of bone resorption compared with the peak tensile stress. 10 Therefore, bone resorption due to overloading should be expected when the compressive stress exceeds 100 to 130MPa in the cortical bone. 21 In the present study, the implant placed at the crestal level (BO model) exerted a peak compressive stress of 233.9 MPa under centric loading, which is above the physiological limit for cortical bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,9 Although a previous study using finite element analysis (FEA) reported that the peak compressive stress at the crestal cortical bone was higher around subcrestal implants than around implants placed at bone level, 10 other studies reported that subcrestal placement displaces the stress away from the crestal cortical bone. 11,12 Therefore, this lower stress concentration in the crestal cortical bone can explain the occurrence of osseointegration coronal to the abutment-fixture interface in cases of subcrestal implant placement with Morse taper connection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is reasonable for clinicians to avoid premature contact, especially premature contact of the pontic when the CFPD is used. Huang et al (2011) revealed that both loading type and implant position were crucial for the stress distribution in bone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when combined with well-designed clinical studies, the results of the current study could guide new strategies for addressing challenges associated with managing stress distribution in implant dentistry. However, the results should be interpreted with caution due to limitations such as factors related to the methodology, computer simulation and linearity elastic analysis, which consider bone tissue to be isotropic and homogenous and apply static occlusal loading (24,25). Therefore, additional controlled and randomized clinical studies should be conducted in order to fully explore and evaluate the clinical implications of various biomechanical parameters in implant dentistry.…”
Section: D Fea Of Implants Varying Diameter and Connectionmentioning
confidence: 99%